2020
DOI: 10.18632/aging.202422
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism at the cornerstone of inflammaging, immunosenescence, and autoimmunity in COVID-19

Abstract: Inflammaging constitutes the common factor for comorbidities predisposing to severe COVID-19. Inflammaging leads to T-cell senescence, and immunosenescence is linked to autoimmune manifestations in COVID-19. As in SLE, metabolic dysregulation occurs in T-cells. Targeting this T-cell dysfunction opens the field for new therapeutic strategies to prevent severe COVID-19. Immunometabolism-mediated approaches such as rapamycin, metformin and dimethyl fumarate, may optimize COVID-19 treatment of the elderly and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 102 publications
2
21
0
Order By: Relevance
“…The consequence of inflame-aging is deleterious effet to organ leading to a higher risk of mortality [21]. Consistent with other studies, our findings reported that patients with higher WBC count, NLR, PCT, D-Dimer, and CRP had higher odds of COVID-19 mortality [5,22,23].…”
Section: Discussionsupporting
confidence: 90%
“…The consequence of inflame-aging is deleterious effet to organ leading to a higher risk of mortality [21]. Consistent with other studies, our findings reported that patients with higher WBC count, NLR, PCT, D-Dimer, and CRP had higher odds of COVID-19 mortality [5,22,23].…”
Section: Discussionsupporting
confidence: 90%
“…Also, it was demonstrated elevated production of INF ȣ by memory T cell from a cohort of MG patients and Th 22 cells, secreting TNF ɑ are increased in MG 19,20 . This is important to know since INF ȣ and TNF ɑ are two components of the cytokine storm observed in ARDS related to SARS‐CoV‐2 infection, 20,21 in addition to immunosenescence, that may contribute to ARDS 13,14 …”
Section: Discussionmentioning
confidence: 98%
“…Inflammaging has since been investigate a whole range of age-related diseases within the so-called “network theory of aging”. Recently, in the pandemic of coronavirus disease 2019 (COVID-19), inflammaging gained additional attention in view of the observed cytokine storm and autoimmunity during infection among older patients, which can result in multiple organ failure and is in general associated with a worse disease outcome [ 135 , 136 ] and of course potentially increases the risk for malnutrition, though data are lacking [ 137 ]. This severe systemic inundation of cytokines might be further triggered by the dysregulated immune system in old age (immunosenescence), which is expressed in an imbalanced homeostasis of pro- and anti-inflammatory mediators [ 135 ].…”
Section: Determinants Of Malnutritionmentioning
confidence: 99%